On Misplaced Narratives of Disaster and Disaster Management: A Review - Sherpa, Pasang; Adhikari, Rudra Narayan (NPRC Journal of Multidisciplinary Research, 2025)
Time and again, Nepal has undergone various kinds of disasters, leading to devastating losses in both human lives and the economy. These calamitous events leave deep scars of pain, loss, suffering and trauma on those vulnerable populations who are directly impacted. While reappraising the disasters, the impact it leaves for the vulnerable population remains short-lived or gets fades away with time, making it nothing to learn from the tragedy they cause. This expository essay centers on the notion of disaster, which is loosely conceived by many in Nepal. Burrowing Miachael Burawoy’s schema of ‘Public Sociology,’ this essay reexamines disaster by shifting its focus from purely ‘natural or technological’ to a ‘social’, thereby engaging a broader audience rather than restricting the discussion to limited academic circles (both social and environmental sciences). By pitching the discussion from the structural dimension of society, the authors argue that the intensity, exigency and fatality associated with disasters are manifestations of societal inequality, structured within ‘social processes’, rather than merely arising from the natural or technological event. Consequently, it is the marginalized groups who lack resources or a voice to influence disaster preparedness (such as women, children, the elderly, the disabled and those below the poverty line) and are the ones who suffer the most.